Peran Komunikasi Organisasi Lembaga MPF Analog Dalam Membangun Relasi Antar Organisasi LAIN - Tarisya Utami Putri; Nadira Rachmadina; Andhika Prasetya Tamtama Putra; Himas Alhani; Jamiati KN (STIKes Ibnu Sina Ajibarang, 2024)
This research discusses the role of organizational communication in MPF Analog institutions in building relationships between other organizations with the aim of exploring the role that affects the success or failure of organizational communication in building relationships or relationships with other organizations. This research uses the literature review method (library research). The quotations in this paper are based on expert opinions and the results of previous research on organizational communication. This research provides insight into how organizational communication can be used as an effective tool for building relationships between organizations and identifies areas for improvement. It includes recommendations for improving communication strategies and the development of stronger inter-organizational interactions.